Domestic violence and the Islamic tradition: ethics, law and the Muslim discourse on gender - Chaudhry, Ayesha S. (Oxford Islamic legal studies, 2013)
Introduction -- I. Historical roots of a contemporary debate. 1. The multiple contexts of Q. 4:34 -- 2. The ethics of wife-beating -- 3. The legal boundaries of marital discipline -- II. Restoring authority in the living community. 4. Asserting authority, enriching tradition -- 5. Submissive texts and idealized cosmologies -- Conclusion.